2013
DOI: 10.4142/jvs.2013.14.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of one-time and two-time intra-articular injection of hyaluronic acid sodium salt after joint surgery in dogs

Abstract: Thirty-one dogs with patellar luxation (grades 2 and 3) were categorized into three groups. Group 1 (G.1; n = 12) had sodium hyaluronate (SHA) intra-articularly injected into the stifle joint that received surgery. Group 2 (G.2; n = 10) received SHA twice: first after surgery and then 1 week later. Group 3 (G.3; n = 9) served as a control, without injection. Blood was collected before injection and then once a week for 4 weeks after injection for evaluation of chondroitin sulfate (CS-WF6) and hyaluronan (HA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Separately, clinical gait scores were assessed using videography to record each animal as they were guided through a predetermined circuit before injection and during week 4 after injection. The animals were subsequently scored clinically according to a schema modified from the veterinary literature (25) (table S2). There was no abnormal gait observed in any of the animals before or after injection.…”
Section: Resultsmentioning
confidence: 99%
“…Separately, clinical gait scores were assessed using videography to record each animal as they were guided through a predetermined circuit before injection and during week 4 after injection. The animals were subsequently scored clinically according to a schema modified from the veterinary literature (25) (table S2). There was no abnormal gait observed in any of the animals before or after injection.…”
Section: Resultsmentioning
confidence: 99%
“…The HA dose administered was based on previous studies in dogs [20, 28]. There is no consensus in the current literature with respect to the required number of IA applications of HA to obtain satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies developed with humans have reported success with a single IA application [29, 30] and with multiple applications at weekly intervals [15, 31]. In dogs undergoing surgical correction of patellar luxation, a single IA application of HA at the end of surgery resulted in similar effects to the application of two doses at weekly intervals [20]. In humans, similar results were reported by Kolarz et al [32], who demonstrated that, in treatment with HA intra-articular injection, single or multiple applications resulted in similar beneficial effects in patients with signs of OA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations